Investigation of deformation of shell with waffle reinforcement during rolling and development of method for compensation of deviations forms - E. V. Krivonos (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
When the waffle panel of AMg6 alloy rolls into the cylindrical shell, a shape defect occurs. Manual elimination of this defect causes local irregularities on butt welded edges of the waffle shell. This leads to difficulties in the process of welding by friction welding with mixing of shells in the section of fuel tanks. It is necessary, on the basis of computer analysis and existing theories, to determine the stresses in the waffle shell that cause internal deformations that result in a general shape error, and to derive patterns under which external influence on the geometry of the mold at the time of bending is possible. The proposed campaign will make it possible to determine auxiliary technological elements for setting standard rolling equipment for defective rolling of wafer shells of missile fuel tanks with various geometric versions of reinforcements. It, in turn, will increase the efficiency of forming shells and the quality of welds when they are welded